E-COMMERCE’S MARKETING STRATEGY TO INCREASE CUSTOMER PREFERENCE AND SATISFACTION - Berlianto, Margaretha Pink (Milestone: Journal of Strategic Management, 2024)
In the midst of increasing e-commerce competition and the dynamics of consumer behavior, industry players need to think strategically to carry out systematic consumer preference research so as not to be left behind in business competition. This research aims to investigate the influence of service quality on brand preference and satisfaction, the influence of perceived risk on brand preference and satisfaction, the influence of perceived price on brand preference and satisfaction, and the influence of brand preference on satisfaction. There were 198 respondents in the research using purposive sampling, namely Lazada consumers who made at least one purchase. The results of this research are that service quality has a positive effect on brand preference and customer satisfaction, perceived risk has no effect on brand preference and customer satisfaction, the price has a positive effect on brand preference but has no effect on customer satisfaction, and brand preference has a positive effect on customer satisfaction. The managerial implication of this research is that e-commerce business players need to focus on service quality because it has the biggest influence on customer preferences and satisfaction.